2015
DOI: 10.1111/jicd.12160
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional accuracy of different techniques used for complete‐arch multi‐implant impressions

Abstract: Casts obtained from the direct nonsplinted transfer impression technique were significantly less accurate than those obtained from the other impression techniques used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Conventional implant impressions were performed with the open tray method (Akalin et al., ; Aldosari, ; Aldosari et al., ; Amin et al., ; de Avila, de Matos Moraes, Castanharo, Del'Acqua, & de Assis Mollo, ; Bergin et al., ; Beyabanaki, Shamshiri, Alikhasi, & Monzavi, ; Buzayan, Baig, & Yunus, ; Di Fiore et al., ; Ehsani et al., ; Geramipanah, Sahebi, Davari, Hajimahmoudi, & Rakhshan, ; Ghahremanloo et al., ; Ghanem, Nassani, Baroudi, & Abdel Fattah, ; Gupta et al., ; Heidari et al., ; Lin et al., ; Marotti et al., ; Ongül et al., ; Ono et al., ; Papaspyridakos et al., ; Perez‐Davidi et al., ; Pozzi et al., ; Pujari, Garg, & Prithviraj, ; Selvaraj, Dorairaj, Mohan & Simon, ; Vigolo, Mutinelli, Fonzi & Stellini, ; Vojdani, Torabi, & Ansarifard, ; Zen et al., ), the closed tray method (Abdel‐Azim et al., ; Calesini et al., ; Del'acqua, de Avila, Amaral, Pinelli, & de Assis Mollo, ; Gökçen‐Rohlig et al., ; Ibrahim, Fouad, Elewa, & Mustafa, ; Ibrahim & Ghuneim, ; Karl et al., ; Lee et al., ; Reddy, Prasad, Vakil, Jain, & Chowdhary, ) or both the open and closed tray methods for comparison of the accuracy (Al Quran et al., ; Alikhasi, Siadat, Beyabanaki, & Kharazifard, ; Alikhasi, Siadat, & Rahimian, ; de Avila, Barros, Del'Acqua, Castanharo, & Mollo Fde, ; BalaMurugan & Manimaran, ; Chang, Vahidi, Bae, & Lim, ; Haghi, Shiehzadeh, Nakhaei, Ahrary, & Sabzevari, ; Hazboun, ; Howell et al., ; Karl & Palarie, ; Mpikos et al., ; Nakhaei, Madani, Moraditalab, & Haghi, ; Ng et al., ; Pera et al., ; Rutkunas, Sveikata, & Savickas, ; Sabouhi et al., , ; ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional implant impressions were performed with the open tray method (Akalin et al., ; Aldosari, ; Aldosari et al., ; Amin et al., ; de Avila, de Matos Moraes, Castanharo, Del'Acqua, & de Assis Mollo, ; Bergin et al., ; Beyabanaki, Shamshiri, Alikhasi, & Monzavi, ; Buzayan, Baig, & Yunus, ; Di Fiore et al., ; Ehsani et al., ; Geramipanah, Sahebi, Davari, Hajimahmoudi, & Rakhshan, ; Ghahremanloo et al., ; Ghanem, Nassani, Baroudi, & Abdel Fattah, ; Gupta et al., ; Heidari et al., ; Lin et al., ; Marotti et al., ; Ongül et al., ; Ono et al., ; Papaspyridakos et al., ; Perez‐Davidi et al., ; Pozzi et al., ; Pujari, Garg, & Prithviraj, ; Selvaraj, Dorairaj, Mohan & Simon, ; Vigolo, Mutinelli, Fonzi & Stellini, ; Vojdani, Torabi, & Ansarifard, ; Zen et al., ), the closed tray method (Abdel‐Azim et al., ; Calesini et al., ; Del'acqua, de Avila, Amaral, Pinelli, & de Assis Mollo, ; Gökçen‐Rohlig et al., ; Ibrahim, Fouad, Elewa, & Mustafa, ; Ibrahim & Ghuneim, ; Karl et al., ; Lee et al., ; Reddy, Prasad, Vakil, Jain, & Chowdhary, ) or both the open and closed tray methods for comparison of the accuracy (Al Quran et al., ; Alikhasi, Siadat, Beyabanaki, & Kharazifard, ; Alikhasi, Siadat, & Rahimian, ; de Avila, Barros, Del'Acqua, Castanharo, & Mollo Fde, ; BalaMurugan & Manimaran, ; Chang, Vahidi, Bae, & Lim, ; Haghi, Shiehzadeh, Nakhaei, Ahrary, & Sabzevari, ; Hazboun, ; Howell et al., ; Karl & Palarie, ; Mpikos et al., ; Nakhaei, Madani, Moraditalab, & Haghi, ; Ng et al., ; Pera et al., ; Rutkunas, Sveikata, & Savickas, ; Sabouhi et al., , ; ...…”
Section: Resultsmentioning
confidence: 99%
“…Impression materials were polyvinylsiloxane, vinylsiloxanether, polyether or condensation silicone. Polyvinylsiloxane materials were used in 26 studies (Abdel‐Azim et al., ; Al‐Abdullah, Zandparsa, Finkelman, & Hirayama, ; Alikhasi, Siadat, Beyabanaki et al., ; Alikhasi, Siadat, & Rahimian, ; de Avila et al., , ; BalaMurugan & Manimaran, ; Beyabanaki et al., ; Calesini et al., ; Del'acqua et al., ; Di Fiore et al., ; Ehsani et al., ; Geramipanah et al., ; Ghahremanloo et al., ; Heidari et al., ; Howell et al., ; Ibrahim et al., ; Lee et al., ; Lin et al., ; Marotti et al., ; Nakhaei et al., ; Ono et al., ; Pozzi et al., ; Sabouhi et al., ; Shim et al., ; Siadat et al., ; Zen et al., ), whereas polyether was used in 22 studies (Al Quran et al., ; Aldosari, ; Aldosari et al., ; Alikhasi, Bassir, & Naini, ; Amin et al., ; Ghanem et al., ; Hazboun, ; Ibrahim & Ghuneim, ; Karl et al., ; Martínez‐Rus et al., ; Mpikos et al., ; Ng et al., ; Ongül et al., ; Papaspyridakos et al., ; Pera et al., ; Perez‐Davidi et al., ; Rashidan, Alikhasi, Samadizadeh, Beyabanaki, & Kharazifard, ; Selvaraj et al., ; Stimmelmayr, Erdelt et al., ; Stimmelmayr, Güth et al., ; Tarib et al., ; Tsagkalidis et al., ; Vigolo et al., ), and vinylsiloxanether and condensation silicone were each used in one study (Eliasson & Ortorp, ). Sixteen studies compared any combination of the aforementioned impression materials (Akalin et al., ; Alikhasi, Siadat, Beyabanaki et al., ; Alikhasi, Siadat, & Rahimian, ; Buzayan et al., ; Chang et al., …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, impressions created with this type of elastomeric impression material can be obtained by different impression techniques [7][8] . Some authors 8,[10][11][12][13][14][15] have demonstrated that the impression technique is a critical factor which directly influences the dimensional accuracy. However, in this study, the dimensional accuracy of a partially edentulous mandibular arch is related more to the type of impression material than the impression technique 7,[16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect the dimensional accuracy of elastomeric impression material molds, such as the type of impression material used and its adhesion to the tray, viscosity, hydrophilicity, thickness, by-product formation, the time spent during cast pouring, incomplete elastic recovery, and polymerization/thermal shrinkage [7][8] . Several studies showing differences in dimensional accuracy between the impression techniques are found in literature [8][9][10][11][12][13][14][15] . Conversely, other studies show similar outcomes between different impression techniques 7,[16][17] or only small differences within a specific group of elastomeric impression materials 18 .…”
Section: Introductionmentioning
confidence: 99%